O tutor em EAD: um metaponto de vista - Almeida, Nadia Josiane Rockenback de (2012)
The issues of the knowing subject gains ground in discussions that guide the processes of teaching and learning over time. Thus, Distance Learning (DL) requires strategies and reflection upon the dimensions that the subject covers for the flexibility of the process. It has as objects the tutor DL. The image of the tutor as an active and creative actor in the interrelations with one another and himself is inserted to the necessity of perception of the complexity of the thought and the changes concerning Education, not disjunct of the functions he carries out as character and subject. It aims the subject-tutor search for comprehension intending to overcome the dichotomized and reductant view that hampers the perception of an integrating character that mobilizes the knowledge. It presents a brief reflection upon Distance Learning, the use of Communication and Information Technologies, the systemic relation that includes them and the tutor-being in this general and specific context. To such purpose, it underlies the Theory of Complexity, by Edgar Morin, based on the notion of the subject and on the hologramatic, recursive and dialogic operator. It was decided to use the qualitative approach with field and bibliographic research to deal with the objects. The chosen method was the non-directed interviews experienced through the guiding question What is to be a DL tutor?" with the use of Skype and an MP3 player as technological resources. The decision was to choose tutors linked to Universidade Aberta do Brasil and Funda????o Centro de Ci??ncias e Educa????o Superior ?? Dist??ncia do Estado do Rio de Janeiro (CECIERJ) courses. The analyses of the interviews present that the tutor is concerned with the functions he puts into practice as a mediator agent and believes that the distance learning, although marked by the harshness and discipline of the educational system, enables a greater proximity to the student and the built knowledge. The results show that the interviewed ones enjoy this kind of teaching and feel as mediators of the teaching/learning process, believe that the DL makes the changes between the pairs possible and feel as if they are still in professional formation. It was concluded that giving the tutors the opportunity to speak was important to understand their tasks and the explicitness of their expectations in the educational field, of their feelings concerning this and the particular mode in which they built each relation, recursively, in and outside themselves.